ANALISIS KADAR FERRITIN SERUM DENGAN NILAI LAJU ENDAP DARAH PADA IBU HAMIL TRIMESTER II - Tia Novita; Nicolaus Sri Widada; Intan Kurniawati Pramitaningrum (Jurnal SainHealth, 2023)
Ferritin examination is an important measurement parameter used to measure the presence of iron in the body. Iron deficiency in the body will result in anemia. Anemia that often occurs in pregnant is iron deficiency anemia because the need for iron in pregnant. An increase in erythrocyte sedimentation rate occurs during pregnancy and can also be observed in pregnant. The purpose of this study was to determine the relationship between serum ferritin levels and the value of ESR in second trimester pregnant. This study was conducted at YPK Mandiri Hospital, samples were in the form of medical record data with 92 samples of second trimester pregnant who performed complete hematological examinations and ferritin levels. The results of this study indicate that second trimester pregnant who do complete blood checks and ferritin levels at YPK Mandiri Hospital with ferritin levels ranging from 2 - 219 ng/mL with an average level of 26.31 ng/mL and the value of the Blood Cessation Rate ranging from 5 - 105 mm / hour with an average of 35 mm / hour. This study uses the Spearman Rho test method, obtained a sig value of 0. 962 (>0.05) with a correlation coefficient of 0.005 which means there is no correlation between ferritin levels and the value of the rate of blood absorption in second trimester pregnant.